2015
DOI: 10.1159/000441216
|View full text |Cite
|
Sign up to set email alerts
|

Confounders of Cardioprotection by Remote Ischemic Preconditioning in Patients Undergoing Coronary Artery Bypass Grafting

Abstract: Objectives: Remote ischemic conditioning (RIC) by repetitive blood pressure cuff inflation/deflation around a limb provides cardioprotection in patients undergoing coronary artery bypass grafting (CABG). Cardioprotection is confounded by risk factors, comorbidities and comedications. We aimed to identify confounders that possibly attenuate the protection provided by RIC. Methods: In a retrospective analysis of our single-center, randomized, double-blind trial of patients undergoing elective CABG with/without R… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
57
0

Year Published

2016
2016
2019
2019

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 47 publications
(60 citation statements)
references
References 35 publications
3
57
0
Order By: Relevance
“…When analyzing this cohort separately for males and females, there was a significant troponin reduction by RIPC only in males. Lack of apparent protection by RIPC in females may also relate to the small sample size, given that in larger cohorts there was no interaction of sex with protection by RIPC in a meta‐analysis of trials in patients with elective percutaneous coronary intervention,35 in a retrospective analysis of the CONDI (Effect of RIC on Clinical Outcomes in STEMI Patients Undergoing pPCI) trial in patients with primary percutaneous coronary intervention,36 and in a retrospective analysis of our previous study in patients undergoing elective bypass surgery 37. Cardioprotection was associated with improved function of mitochondria, confirming the notion that mitochondria are a target of RIPC's protection.…”
Section: Discussionmentioning
confidence: 99%
“…When analyzing this cohort separately for males and females, there was a significant troponin reduction by RIPC only in males. Lack of apparent protection by RIPC in females may also relate to the small sample size, given that in larger cohorts there was no interaction of sex with protection by RIPC in a meta‐analysis of trials in patients with elective percutaneous coronary intervention,35 in a retrospective analysis of the CONDI (Effect of RIC on Clinical Outcomes in STEMI Patients Undergoing pPCI) trial in patients with primary percutaneous coronary intervention,36 and in a retrospective analysis of our previous study in patients undergoing elective bypass surgery 37. Cardioprotection was associated with improved function of mitochondria, confirming the notion that mitochondria are a target of RIPC's protection.…”
Section: Discussionmentioning
confidence: 99%
“…175 Aging per se attenuates cardioprotective signaling, [176][177][178] although in 2 retrospective analyses for confounders, protection by remote ischemic preconditioning was seen in all age cohorts of patients undergoing surgical coronary revascularization 179 and protection by remote ischemic perconditioning was seen n.s. P P P P P P P P P P P P P P P P P in all age cohorts of patients with acute STEMI undergoing primary PCI.…”
Section: Lack Of Comorbidities and Comedications In Animal Experimentsmentioning
confidence: 99%
“…19,230,231 On the contrary, with a short duration of ischemia, all ischemic myocardium may be rescued by reperfusion per se, and an additional cardioprotection may be difficult to demonstrate. 20,179,231 Also, with a short duration of ischemia, ischemic postconditioning may even add to myocardial injury.…”
Section: Translation From Proof-of-concept Studies To Larger Trials Wmentioning
confidence: 99%
See 1 more Smart Citation
“…In addition to the possible confounding effect of diabetes mellitus and other comorbidities, 14 there is evidence that the magnitude of cardioprotection achieved with RIC is proportional to the ischemic burden. 6,15,16 Specifically, in patients undergoing CABG, recent retrospective analysis revealed that RIC evoked significant reductions in troponin I release with cross-clamp times >57 minutes, but had no effect with ischemic durations ≤56 minutes. 16 Accordingly, in cohorts undergoing elective cardiac surgeries, with crossclamp times as short as 18 minutes in the ERICCA trial, 8 and in which myocardial ischemia-reperfusion injury may have already been blunted by cardioplegia, hypothermia and, in subsets of patients, volatile anesthetics and opioids, the scope for improvement with RIC may have been modest at best.…”
Section: Disappointing But Predictable?mentioning
confidence: 99%